Screening method of recycled graphite and manufacturing method of negative plate

Through the multiple screening steps of the graphite recycling screening method, the problem of long time and high cost in the existing technology of recycling graphite recycling is solved, and the effect of rapid screening of qualified graphite is achieved, reducing battery costs and improving development efficiency is achieved.

CN119819592APending Publication Date: 2025-04-15BATTEROTECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411907771.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

When screening and recycling graphite, the process time is long and the cost is high, making it difficult to meet the price positioning of low-speed two-wheeled vehicles and other application scenarios.

Method used

Provide a screening method for recycling graphite, which can quickly eliminate unqualified products through multiple screening steps (including carbon coating screening, particle size distribution, tap density, specific surface area, gram capacity and first-effect screening, graphitization degree and residual carbon volume screening), improve screening efficiency and reduce costs.

Benefits of technology

This method can be used to screen qualified recycling graphite in a short time, reduce the cost of lithium-ion batteries, improve product development efficiency, and is suitable for application scenarios such as low-speed two-wheeled vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819592A_ABST
    Figure CN119819592A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a screening method of recycled graphite and a manufacturing method of a negative plate. The screening method provided by the invention comprises the following steps: carrying out primary screening according to whether the recycled graphite is subjected to carbon coating or not, and screening out the carbon-coated recycled graphite; the recycled graphite obtained after primary screening is subjected to secondary screening, and the indexes of secondary screening are particle size distribution, tap density, specific surface area, gram volume and first effect; the recycled graphite obtained after secondary screening is subjected to third-time screening, and indexes of third-time screening are Dv10, Dv50 and Dv90 graphitization degrees and residual carbon amount; the recycled graphite screened for three times is adopted to manufacture a negative plate and matched with a positive plate to manufacture a soft package battery cell, and whether the soft package battery cell is selected or not is determined according to an electrochemical test result. According to the screening method for the recycled graphite, the screening efficiency can be improved, the trial and error cost can be reduced, and the manufacturing cost and the use cost of the lithium ion battery can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a method for screening recycled graphite and a method for manufacturing a negative electrode sheet. Background Art

[0002] At present, the lithium-ion battery market pays more and more attention to cost control, which has spawned many low-cost application scenarios, such as the low-speed two-wheeled vehicle market. Although lithium-ion batteries have advantages over conventional lead-acid batteries, such as high energy density, light weight, fast charging speed, and long life, their costs are also relatively high. High-priced lithium-ion batteries cannot meet the price positioning of low-speed two-wheeled vehicles. Therefore, while taking into account performance, reducing the cost of lithium-ion batteries will help the large-scale promotion and application of lithium-ion batteries in application scenarios such as low-speed two-wheeled vehicles.

[0003] As one of the four main materials of lithium-ion batteries, negative electrode graphite accounts for a relatively high proportion of costs. Currently, the use of recycled graphite is a solution that can keep costs to a minimum. The quality of recycled graphite directly affects the quality of the battery cell. Some recycled graphite only meets the cost requirements, and the unreasonable physical and chemical parameters lead to poor electrical performance and cannot be truly applied to battery cell products. Therefore, the screening of recycled graphite is crucial.

[0004] At present, the evaluation of the quality of recycled graphite is to make the recycled graphite into negative electrode sheets and match them with corresponding positive electrode sheets, and then obtain the soft-pack cells required for testing through the steps of lamination, hot pressing, welding, shelling, baking, liquid injection, formation, and capacity division. Then, the soft-pack cells are electrochemically tested. This process takes a long time and is also costly. If each batch of graphite is electrochemically tested through soft-pack cells, it will undoubtedly take a long time and cost a lot. Summary of the invention

[0005] The present application provides a method for screening recycled graphite and a method for making a negative electrode sheet, which can relatively quickly screen out qualified recycled graphite, save users' time and cost in screening recycled graphite, and reduce the use cost of lithium-ion batteries.

[0006] The technical solutions of this application are as follows:

[0007] In a first aspect, the present application provides a method for screening recycled graphite, comprising the following steps:

[0008] S1) screening is performed according to whether the recovered graphite is carbon-coated, and the recovered graphite that has been carbon-coated is screened out.

[0009] S2) The recycled graphite screened out in the first screening is subjected to a second screening, and the indicators of the second screening are: particle size distribution, tap density, specific surface area, gram capacity and first efficiency.

[0010] The recycled graphite screened out for the second time meets at least two indicators of particle size distribution, tap density, specific surface area, gram capacity and first efficiency.

[0011] The particle size distribution is recorded as D, D = (Dv90-Dv10) / Dv50, Dv10 means that 10% of the particles on the cumulative distribution curve are smaller than this particle size. Dv50 means that 50% of the particles on the cumulative distribution curve are smaller than this particle size. Dv90 means that 90% of the particles on the cumulative distribution curve are smaller than this particle size.

[0012] S3) The recycled graphite screened out from the secondary screening is screened for a third time, and the indicators of the third screening are: Dv10, Dv50, Dv90 graphitization degree and residual carbon content.

[0013] The recycled graphite screened three times must meet the index requirements of Dv50 and at least two of the indicators of Dv10, Dv90, degree of graphitization and residual carbon content.

[0014] S4) The recycled graphite screened out three times is used to make negative electrode sheets, and is matched with positive electrode sheets to make soft-pack batteries, and electrochemical tests are performed to determine whether to use it or not based on the electrochemical test results.

[0015] Through the method for screening recycled graphite of the present application, unqualified products can be quickly screened out through steps S1) to S3), thereby improving the screening efficiency and saving various manpower and material costs required in the production process of soft-pack battery cells. The more batches of recycled graphite that need to be screened, the more significant the effect of the present application.

[0016] In addition, after screening from step S1) to step S3), the qualified rate of the recycled graphite that enters the test of step S4) is about 90%. Therefore, through steps S1) to S3) of the graphite screening method proposed in this application, relevant personnel can judge the performance of the recycled graphite in advance, reduce the cost of trial and error, and improve the efficiency of product development.

[0017] In one possible design, in step S2):

[0018] D=1.4-1.8.

[0019] The tap density is recorded as TD, TD ≥ 0.95 g / cm 3 .

[0020] The specific surface area is recorded as SSA, SSA ≤ 2.0m 2 / g.

[0021] The gram capacity is recorded as C, C ≥ 340 mAh / g.

[0022] The first effect was recorded as CE, and CE≥92.0%.

[0023] Through the screening method for recycled graphite provided by this embodiment, for similar application scenarios such as low-speed two-wheeled vehicles, this application provides specific reference values ​​for particle size distribution, tap density, specific surface area, gram capacity, and first effect. Those skilled in the art can screen the recycled graphite according to the specific powder parameters. In this way, the cost of lithium-ion batteries can be reduced while taking into account the performance, which is conducive to the large-scale promotion and application of lithium-ion batteries in application scenarios such as low-speed two-wheeled vehicles.

[0024] In a possible design, in step S3), Dv10≥5um, 11.5um≤Dv50≤15.5um, 24um≤Dv90≤35um, graphitization degree≥93.0%, 1.0%≤residual carbon content≤3.0%.

[0025] Based on the screening method of recycled graphite provided in this embodiment and the performance requirements of the above-mentioned specific battery cells, this application provides specific reference values ​​of Dv10, Dv50, Dv90, degree of graphitization and residual carbon, so that those skilled in the art can screen recycled graphite according to specific powder parameters, reduce trial and error costs, and improve product development efficiency. Recycled graphite that meets the above conditions has good kinetic performance and cycle performance, which will be verified later through the test results of specific embodiments.

[0026] In a possible design, in step S2), the three screening indicators also include key powder parameter A.

[0027]

[0028] Wherein, D represents particle size distribution, TD represents tap density, SSA represents specific surface area, C represents gram capacity, and CE represents first effect.

[0029] Based on the screening method for recycled graphite provided in this embodiment, relevant users can not only screen out qualified recycled graphite through the screening method provided in this application, but also screen out recycled graphite with better performance.

[0030] In one possible design, the key powder parameter A ≥ 5.27.

[0031] In one possible design, TD ≥ 1.05 g / cm 3 , SSA≤1.8m 2 / g, C≥343mAh / g, CE≥93.0%, the recycled graphite meeting this group of performance indicators has good cycle performance and kinetic performance.

[0032] In a possible design, Dv10≥6um, 12.5um≤Dv50≤14.5um, 26um≤Dv90≤30um, graphitization degree≥93.5%, 1.5≤residual carbon content≤2.5%. The recycled graphite meeting this group of performance indicators has good cycle performance and kinetic performance.

[0033] In a second aspect, based on the same inventive concept, the present invention also provides a method for making a negative electrode sheet using the recycled graphite screened by the above screening method, comprising the following steps:

[0034] J1) The recovered graphite, dispersant, conductive agent, binder and solvent are homogenized according to processing requirements to obtain negative electrode slurry.

[0035] J2) The negative electrode slurry is coated on the current collector, baked in an oven, and then roll-pressed. After striping and die-cutting according to specifications, the desired negative electrode sheet is obtained.

[0036] Based on the method for making negative electrode sheets provided in the second aspect, the recycled graphite screened out by the screening method of the present application can be used to make negative electrode sheets through the existing conventional negative electrode sheet making steps. In this way, when using recycled graphite to make negative electrode sheets, there is no need to develop new process steps or adopt new equipment, which is conducive to reducing costs.

[0037] In a possible design, in step J1), the dispersant is CMC, the conductive agent is Super P, and the binder is SBR.

[0038] By mass percentage: recycled graphite: SUPER P: CMC: SBR = 96.2%: 0.8%: 1.2%: 1.8%, and the solvent is deionized water.

[0039] In step J1), the negative electrode slurry has a delivery viscosity of 2000-8000 mPa*s, a solid content of 42-46%, and a delivery fluidity of 0.5-3 min / kg. In step J2), the compaction density of the negative electrode slurry is 1.5-1.6 g / cc.

[0040] Based on the method for making the negative electrode sheet provided in this embodiment, the dispersant, conductive agent, and binder used are all conventionally used substances in the field, the ratio of graphite, SUPER P, CMC, and SBR is also a conventional ratio, and the slurry shipping viscosity, solid content, and shipping fluidity are also conventional settings. In this way, the recycled graphite screened out by the screening method of this application can not only be made using conventional preparation steps, but other related raw materials and process parameters can also refer to the existing primary graphite process, which is more conducive to reducing costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1It is a comparison chart of the results of the normal temperature 25° C. cycle tests of Example 1, Example 2, Example 10, Example 14 and Comparative Examples 1 to Comparative Examples 4;

[0042] Figure 2 It is a comparison chart of high temperature 45°C cycle test results of Example 1, Example 2, Example 10, Example 14 and Comparative Examples 1 to Comparative Examples 4;

[0043] Figure 3 It is a comparison chart of the discharge DCR test results of Example 1, Example 2, Example 10, Example 14 and Comparative Examples 1 to Comparative Examples 4. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0045] The embodiments given in this application can be combined with each other if no contradiction occurs. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0046] All raw materials used in this application have no particular limitation on their sources and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0047] All raw materials used in the present application, unless otherwise specified, are raw materials commonly used in the art, and those skilled in the art can purchase them commercially or prepare them using conventional methods based on the names of the raw materials and their corresponding uses.

[0048] The abbreviations of the processes used in this application are all conventional abbreviations in the field. The specific steps and conventional parameters of each abbreviation are clear and definite in its relevant field, and those skilled in the art can implement them in a conventional manner based on the abbreviations.

[0049] Unless otherwise defined, all terms used herein have the same meanings as commonly understood by those skilled in the art unless otherwise specified.

[0050] The following is a detailed description of this application.

[0051] Incoming inspection of negative electrode materials is crucial to the quality control of battery cells. Currently, there are two major challenges in the inspection of recycled graphite:

[0052] First: There is a lack of corresponding powder reference indicators. At present, there are national standards for the powder indicators of natural graphite and artificial graphite. However, there are no corresponding standards for recycled graphite. The powder standards of natural graphite and artificial graphite are not applicable to recycled graphite.

[0053] Second: There are many graphite powder parameters. The degree of influence of each powder parameter on the performance of the battery cell is unclear. At present, it is difficult for technicians to determine whether the recycled graphite is usable based on the powder parameters.

[0054] Based on the above situation, the current test for recycled graphite is to directly make the recycled graphite into negative electrode sheets, and match them with corresponding positive electrode sheets, and then go through the steps of lamination, hot pressing, welding, shelling, baking, liquid injection, formation, and capacity division in sequence to obtain the soft-pack battery cells required for the test. Then, the soft-pack battery cells are electrochemically tested. This process takes a long time and is also costly.

[0055] In order to reduce the inspection time of recycled graphite, improve inspection efficiency and reduce costs, the present application provides a screening method for recycled graphite, comprising the following steps:

[0056] S1) screening is performed according to whether the recovered graphite is carbon-coated, and the recovered graphite that has been carbon-coated is screened out.

[0057] S2) The recycled graphite screened out in the first screening is subjected to a second screening, and the indicators of the second screening are: particle size distribution, tap density, specific surface area, gram capacity and first efficiency.

[0058] The recycled graphite screened out for the second time meets at least two indicators of particle size distribution, tap density, specific surface area, gram capacity and first efficiency.

[0059] The particle size distribution is recorded as D, D = (Dv90-Dv10) / Dv50, Dv10 means that 10% of the particles on the cumulative distribution curve are smaller than this particle size. Dv50 means that 50% of the particles on the cumulative distribution curve are smaller than this particle size. Dv90 means that 90% of the particles on the cumulative distribution curve are smaller than this particle size.

[0060] S3) The recycled graphite screened out from the secondary screening is screened for a third time, and the indicators of the third screening are: Dv10, Dv50, Dv90 graphitization degree and residual carbon content.

[0061] The recycled graphite screened three times must meet the index requirements of Dv50 and at least two of the indicators of Dv10, Dv90, degree of graphitization and residual carbon content.

[0062] S4) The recycled graphite screened out three times is used to make negative electrode sheets, and is matched with positive electrode sheets to make soft-pack batteries, and electrochemical tests are performed to determine whether to use it or not based on the electrochemical test results.

[0063] It should be noted that the source of the recycled graphite mentioned in this application is the graphite negative electrode sheet that has not been injected with liquid.

[0064] The screening method for recovered graphite provided in the present application can greatly save the screening efficiency of recovered graphite when used for the inspection of recovered graphite, which is specifically manifested as follows:

[0065] According to the applicant's experience, the specific surface area of ​​uncoated recycled graphite is mostly poor, and the performance indicators of the final manufactured battery cells are mostly unsatisfactory. Therefore, the screening method of this application first eliminates uncoated recycled graphite. Whether the recycled graphite is carbon-coated can be learned by querying the supply information of the recycled graphite or asking the supplier directly.

[0066] The screening in step S2) and step S3) are both based on the powder indicators of the recovered graphite. The inspection of these indicators can be carried out in the laboratory, which takes a total of about 24 hours.

[0067] The screening of step S4) is the most time-consuming. Generally speaking, the recycled graphite needs to be made into a negative electrode sheet first, and then matched with the corresponding positive electrode sheet, and then a series of processes are used to produce the soft-pack battery required for the test. Then, the soft-pack battery is electrochemically tested. The electrochemical test items generally include life tests and kinetic tests. Among them, the production of the soft-pack battery takes about 3 days, 160 days for normal temperature cycling to 2000 cycles, and 100 days for high temperature cycling to 1200 cycles. The S4) step takes more than two months in total.

[0068] During the inspection process, it was found that the total qualified rate of recycled graphite was about 30%, the qualified rate of the first screening was about 70%, the qualified rate of the second screening was 57%, and the qualified rate of the third screening was 75%.

[0069] For example: 10 types of recycled graphite need to be evaluated. After step S1), 3 types are eliminated and 7 types are screened out. After step S2), 3 types are eliminated and 4 types are screened out. After step S3), 1 type is eliminated and 3 types are screened out. Finally, only 2 types of recycled graphite enter step S4).

[0070] Through the above description and comparison, the screening method for recycled graphite provided in the present application can quickly screen out unqualified products through steps S1) to S3), thereby improving the screening efficiency and saving various manpower and material costs required in the production process of soft-pack battery cells. Moreover, as more batches of recycled graphite are screened, the more significant the effect of the present application is.

[0071] In addition, after screening from step S1) to step S3), the qualified rate of the recycled graphite that enters the test of step S4) is about 90%. Therefore, through steps S1) to S3) of the graphite screening method proposed in this application, relevant personnel can judge the performance of the recycled graphite in advance, reduce the cost of trial and error, and improve the efficiency of product development.

[0072] As mentioned in the background technology, the cost of lithium-ion batteries is high and it is difficult to meet the needs of some application scenarios. The use of recycled graphite can reduce costs. Then, the performance requirements of lithium-ion batteries in different application scenarios will also be different. For example, in similar scenarios such as low-speed two-wheeled vehicles: the performance indicators of lithium-ion batteries are: 2000 cycles at room temperature 25°C (80% capacity retention rate), 1200 cycles at high temperature 45°C (80% capacity retention rate), 50% SOC-DCR≤20, 10% SOC-DCR≤30, 90% SOC-DCR≤18.

[0073] For this scenario, the method of the present application can also be applied to quickly screen out suitable recycled graphite. Wherein, in step S2), D=1.4-1.8.

[0074] The tap density is recorded as TD, TD≥0.95g / cm3.

[0075] The specific surface area is recorded as SSA, SSA ≤ 2.0 m2 / g.

[0076] The gram capacity is recorded as C, C ≥ 340 mAh / g.

[0077] The first effect was recorded as CE, and CE≥92.0%.

[0078] It should be noted that, in this embodiment, Dv10, Dv50 and Dv90 are tested according to GB / T 19077.1-2016. The test method of tap density is tested in accordance with Appendix M of GB / T 24533-2019, the test method of specific surface area is tested in accordance with GB / T 19587-2017 "Determination of Specific Surface Area of ​​Solid Substances by Gas Adsorption BET Method", and the test methods of gram capacity and first effect are tested in accordance with Appendix G of GB / T 24533-2019.

[0079] In summary, based on the screening method for recycled graphite provided in this embodiment, for similar application scenarios such as low-speed two-wheeled vehicles, this application provides specific reference values ​​for particle size distribution, tap density, specific surface area, gram capacity, and first effect. Those skilled in the art can screen the recycled graphite according to the specific powder parameters. In this way, the cost of lithium-ion batteries can be reduced while taking into account the performance, which is conducive to the large-scale promotion and application of lithium-ion batteries in application scenarios such as low-speed two-wheeled vehicles.

[0080] Further, the performance index requirements are: normal temperature 25°C cycle ≥ 2000 cycles (80% capacity retention rate), high temperature 45°C cycle ≥ 1200 cycles (80% capacity retention rate), 50% SOC-DCR ≤ 20, 10% SOC-DCR ≤ 30, 90% SOC-DCR ≤ 18 lithium-ion battery. In step S3), Dv10 ≥ 5um, 11.5um ≤ Dv50 ≤ 15.5um, 24um ≤ Dv90 ≤ 35um, graphitization degree ≥ 93.0%, 1.0% ≤ residual carbon content ≤ 3.0%.

[0081] It should be noted that, in this embodiment, the test method for graphitization degree is based on Appendix E of GB / T 24533-2019, and the test method for residual carbon content adopts coating agent addition amount*coking value.

[0082] In summary, based on the screening method for recycled graphite provided in this embodiment and based on the performance requirements of the above-mentioned specific battery cells, this application provides specific reference values ​​for Dv10, Dv50, Dv90, degree of graphitization and residual carbon, so that those skilled in the art can screen recycled graphite according to specific powder parameters, reduce trial and error costs, and improve product development efficiency. Recycled graphite that meets the above conditions has good kinetic performance and cycle performance, which will be verified later through the test results of specific embodiments.

[0083] Specifically, in some scenarios, multiple batches of recycled graphite are predicted to meet the performance requirements of the target battery cells. If further selection is required, a screening index can be added in step S3), and the added index is the key powder parameter A.

[0084]

[0085] Wherein, D represents particle size distribution, TD represents tap density, SSA represents specific surface area, C represents gram capacity, and CE represents first effect.

[0086] It should be noted that the D, TD, TD, C, SSA, and CE used to calculate the key powder parameter A are the same as the corresponding indicators in step S2). The numerator of the calculation formula of the key powder parameter A is a parameter that has a positive impact on the performance of the battery cell, and the denominator of the calculation formula of the key powder parameter A is a parameter that has a negative impact on the performance of the battery cell. The inventors have given corresponding coefficients to C and SSA in the calculation formula of A based on the different degrees of influence of D, TD, SSA, C, and CE on the performance of the battery cell. The larger the key powder parameter A, the better the performance of the target battery cell.

[0087] It can be seen from the above that based on the screening method for recycled graphite provided in this embodiment, relevant users can not only screen out qualified recycled graphite through the screening method provided in this application, but also screen out recycled graphite with better performance.

[0088] Furthermore, the performance index requirements are: 25°C cycle ≥ 2000 cycles (80% capacity retention rate), 45°C cycle ≥ 1200 cycles (80% capacity retention rate), 50% SOC-DCR ≤ 20, 10% SOC-DCR ≤ 30, 90% SOC-DCR ≤ 18 for lithium-ion batteries. The key powder parameter A ≥ 5.27.

[0089] In some embodiments of the present application, the performance index requirements are: 25°C room temperature cycle ≥ 2000 cycles (80% capacity retention rate), high temperature 45°C cycle ≥ 1200 cycles (80% capacity retention rate), 50% SOC-DCR ≤ 20, 10% SOC-DCR ≤ 30, 90% SOC-DCR ≤ 18 lithium-ion batteries. A set of better powder parameters is: TD ≥ 1.05 g / cm 3 , SSA≤1.8m 2 / g, C≥343mAh / g, CE≥93.0%.

[0090] In some embodiments of the present application, the performance index requirements are: 25°C room temperature cycle ≥ 2000 cycles (80% capacity retention rate), high temperature 45°C cycle ≥ 1200 cycles (80% capacity retention rate), 50% SOC-DCR ≤ 20, 10% SOC-DCR ≤ 30, 90% SOC-DCR ≤ 18 lithium-ion batteries. A set of preferred powder parameters are: Dv10 ≥ 6um, 12.5um ≤ Dv50 ≤ 14.5um, 26um ≤ Dv90 ≤ 30um, graphitization degree ≥ 93.5%, 1.5 ≤ residual carbon content ≤ 2.5%.

[0091] For lithium-ion batteries with performance index requirements of: 2000 cycles at room temperature 25°C (80% capacity retention), 1200 cycles at high temperature 45°C (80% capacity retention), 50% SOC-DCR≤20, 10% SOC-DCR≤30, 90% SOC-DCR≤18. The present application also provides a method for making a negative electrode sheet using the screened recycled graphite, comprising the following steps:

[0092] J1) The recovered graphite, dispersant, conductive agent, binder and solvent are homogenized according to processing requirements to obtain negative electrode slurry.

[0093] J2) The negative electrode slurry is coated on the current collector, baked in an oven, and then roll-pressed. After striping and die-cutting according to specifications, the desired negative electrode sheet is obtained.

[0094] It can be seen from the above steps of making negative electrode sheets that the recycled graphite screened out by the screening method of the present application can be used to make negative electrode sheets through the existing conventional negative electrode sheet making steps. In this way, when using recycled graphite to make negative electrode sheets, there is no need to develop new process steps or adopt new equipment, which is conducive to reducing costs.

[0095] In some embodiments of the present application, in step J1), the dispersant is CMC, the conductive agent is Super P, and the binder is SBR.

[0096] By mass percentage: graphite: SUPER P: CMC: SBR = 96.2%: 0.8%: 1.2%: 1.8%, and the solvent is deionized water.

[0097] In step J1), the negative electrode slurry has a delivery viscosity of 2000-8000 mPa*s, a solid content of 42-46%, and a delivery fluidity of 0.5-3 min / kg.

[0098] In step J2), the compaction density of the negative electrode slurry after roller pressing is 1.5-1.6 g / cc.

[0099] Specifically, in the above embodiment, the dispersant, conductive agent, and binder used are all conventional materials used in the art, and the ratios of graphite, SUPER P, CMC, and SBR are also conventional ratios, and the slurry shipping viscosity, solid content, and shipping fluidity are also conventional settings. In this way, the recovered graphite screened out by the screening method of the present application can not only be made using conventional preparation steps, but also other related raw materials and process parameters can also refer to the existing primary graphite process, so it is more conducive to reducing costs.

[0100] In order to further verify the effectiveness of the graphite recovery screening method provided in the present application, it is verified through specific examples and comparative examples below.

[0101] Embodiment 1:

[0102] The basic indicators of the recovered graphite screened by step S1) to step S3) are as follows: Dv10 = 5.5um, Dv50 = 12.8um, Dv90 = 26.8um, particle size distribution (Dv90-Dv10) / Dv50 = 1.66, tap density = 1.07g / cm 3 , specific surface area = 1.82m 2 / g, graphitization degree = 93.8%, gram capacity = 345.2mAh / g, first efficiency = 93.00%, residual carbon content 1.80%. The key powder parameter A is 6.48.

[0103] The recycled graphite, dispersant, conductive agent, binder and solvent selected in step S3) are homogenized according to the processing requirements to obtain negative electrode slurry. Among them, the dispersant is CMC, the conductive agent is Super P, the binder is SBR, the main material: SUPER P: CMC: SBR ratio is 96.2%: 0.8%: 1.2%: 1.8%, and the solvent is deionized water. The slurry has a shipping viscosity of 4570mPa*s, a solid content of 44.3%, and a shipping fluidity of 0.6min / kg.

[0104] The negative electrode slurry is coated on the current collector copper foil, baked in an oven, and rolled to a compaction density of 1.55 g / cc. After being striped and die-cut according to specifications, the required negative electrode sheet is obtained.

[0105] The obtained negative electrode sheet is matched with the corresponding LFP positive electrode sheet, and the soft-pack battery cell required for the test is obtained through the steps of lamination, hot pressing, welding, shelling, baking, liquid injection, formation, and capacity division.

[0106] Other examples and comparative examples are shown in Table 1 below:

[0107] Table 1:

[0108]

[0109]

[0110] Example 2 to Example 14 and Comparative Example 1 to Comparative Example 4:

[0111] Examples 2 to 14 and Comparative Examples 1 to 4 adopt the same screening method as Example 1, and adopt the same soft-pack battery cell manufacturing process to manufacture soft-pack batteries. Among them, Examples 2 to 14 are qualified products screened out by steps S1) to S3) of the screening method of this application, and Comparative Examples 1 to 4 are unqualified products screened out by steps S1) to S3) of the screening method of this application.

[0112] Soft pack battery performance test:

[0113] The soft-pack cells prepared in Examples 1 to 14 and Comparative Examples 1 to 4 were subjected to normal temperature cycle, high temperature cycle, and discharge DCR tests:

[0114] 1. Normal temperature cycle: At 25°C, perform 1C charge and discharge test on the soft-pack battery cell with 0.33C standard capacity in the voltage window of 2.5-3.65V. The first 1C discharge capacity is recorded as the starting capacity C, the discharge capacity after n cycles is recorded as Cn, and Cn / C is calculated as the normal temperature capacity retention rate. When the test state is 600 cycles, the capacity retention rate is greater than 100%, and the normal temperature cycle performance is high. The capacity retention rate is between 98-100%, and the normal temperature cycle performance is medium. The normal temperature capacity retention rate is less than 98%, and the normal temperature cycle performance is low.

[0115] 2. High temperature cycle: At 45°C, perform 1C charge and discharge test on the battery cell with 0.33C standard capacity in the voltage window of 2.5-3.65V. The first 1C discharge capacity is recorded as the starting capacity C, and the discharge capacity after n cycles is recorded as Cn. Cn / C is calculated and recorded as the normal temperature capacity retention rate. When the test state is 400 cycles, the capacity retention rate is greater than 93%, and the high temperature cycle performance is high. The capacity retention rate is between 92-93%, and the normal temperature cycle performance is medium. The normal temperature capacity retention rate is less than 92%, and the normal temperature cycle performance is low.

[0116] 3. Discharge DCR: At 25°C, the DCR test is performed on the battery cells with 0.33C standard capacity at different SOCs (10%, 50%, 90%), the test rate is 2C, the test time is 30s, and (shelf end voltage-discharge end voltage) / discharge current is recorded as the discharge DCR at the current state of charge. When the test state is 10% SOC, DCR < 25mohm, the dynamic performance is high, DCR is 25-30mohm, the dynamic performance is medium, DCR > 30mohm, and the dynamic performance is low. When the test state is 50% SOC, DCR < 16mohm, the dynamic performance is high, DCR is 16-20mohm, the dynamic performance is medium, DCR > 20mohm, and the dynamic performance is low. When the test state is 90% SOC, DCR < 15mohm, the dynamic performance is high, DCR is 15-18mohm, the dynamic performance is medium, DCR > 18mohm, and the dynamic performance is low.

[0117] The test results of the soft-packed cells prepared in Examples 1 to 14 and Comparative Examples 1 to 4 are shown in Table 2 below.

[0118]

[0119]

[0120] Note: In Table 2, the unit of life is cycles and the unit of DCR is mohm.

[0121] The index evaluation of the soft-packed cells prepared in Examples 1 to 14 and Comparative Examples 1 to 4 is shown in Table 3 below. Table 3:

[0122]

[0123]

[0124] Test result analysis:

[0125] The performance requirements of the target battery cell are: ≥2000 cycles at room temperature 25°C (80% capacity retention rate), ≥1200 cycles at high temperature 45°C (80% capacity retention rate), 50% SOC-DCR≤20, 10% SOC-DCR≤30, 90% SOC-DCR≤18 for lithium-ion batteries.

[0126] Examples 1 to 14 are based on the powder indicators provided in this application, and qualified recycled graphite screened out according to the screening method of this application, and are made into negative electrode sheets using the process provided in this application, and assembled into soft-pack batteries. According to the test results in Table 2, the performance indicators of Examples 1 to 14 can meet the requirements of the target battery.

[0127] Comparative Examples 1 to 4 are based on the powder indicators provided in this application, unqualified recycled graphite screened out according to the screening method of this application, and the negative electrode sheets are made using the process provided in this application, and assembled into soft-pack batteries. According to the test results in Table 2, most performance indicators of Comparative Examples 1 to 4 cannot meet the requirements of the target battery.

[0128] It can be seen from the above that, through the screening method for recycled graphite provided in the present application, the screening of steps S1) to S3) is effective. Thus, in practice, relevant personnel can predict the performance of recycled graphite according to the recycled graphite powder indicators provided in the present application. In this way, the trial and error cost can be reduced, a lot of time can be saved, product development efficiency can be improved, and costs can be reduced.

[0129] Please combine Table 1 and Table 3. It can be seen intuitively from Table 3 that the larger the key powder parameter A is, the higher the corresponding performance index rating is, and the better the overall performance is. In this way, relevant personnel can compare the performance of various recycled graphites based on the key powder parameter A.

[0130] Combined with Table 1, Table 2, Figure 1 , Figure 2 and Figure 3It can be known that if the powder index of the screened recycled graphite is more consistent with the screening index provided in this application, the performance of the final product will be better, such as Example 1 and Example 2; if two of the particle size distribution, tap density, specific surface area, gram capacity and first effect of the recycled graphite meet the index requirements, and Dv50 meets the index requirements, and two of the graphitization degree and residual carbon content of Dv10 and Dv90 meet the index requirements, then the recycled graphite as a whole also meets the requirements, but the cycle performance and kinetic performance of the final product are slightly worse, but also meet the use requirements, such as Example 10 and Example 14.

[0131] If only one of the particle size distribution, tap density, specific surface area, gram capacity and first efficiency of the recycled graphite meets the index requirements and does not meet the screening requirements of step S2), the test results also show that the cycle performance or kinetic performance of the final product is very poor and cannot be used, such as Comparative Examples 1 to 4.

[0132] Please refer to Figure 2 In the high temperature cycle test, the performance of Example 10 and Example 14 is slightly weaker, but also meets the index requirements of the target battery cell; it is worth noting that the high temperature cycle performance of Comparative Examples 1 and Comparative Examples 4 is better than that of Example 10 and Example 14.

[0133] Please refer to Figure 1 and Figure 3 ,according to Figure 1 and Figure 3 It is shown that although the performance of Example 10 and Example 14 is not as good as that of Example 1 and Example 2, the room temperature cycle performance and dynamic performance are better than those of Comparative Examples 1 to 4.

[0134] comprehensive Figure 1 , Figure 2 and Figure 3 It can be seen that the good performance of recycled graphite in one aspect does not mean that the performance in other aspects is correspondingly good, such as Comparative Examples 1 and 4. Figure 1 and Figure 3 It can be seen that the recycled graphite that meets the screening requirements of this application has better overall performance.

Claims

1. A method for screening recycled graphite, characterized in that: The steps include: S1) screening is performed according to whether the recovered graphite is carbon-coated, and the recovered graphite that has been carbon-coated is screened out; S2) performing secondary screening on the recovered graphite screened out of the primary screening, wherein the secondary screening indicators are: particle size distribution, tap density, specific surface area, gram capacity and first efficiency; The recycled graphite screened out from the secondary screening meets at least two of the following indicators: particle size distribution, tap density, specific surface area, gram capacity, and first efficiency; The particle size distribution is recorded as D, D = (Dv90-Dv10) / Dv50, Dv10 means that 10% of the particles on the cumulative distribution curve are smaller than the particle size; Dv50 means that 50% of the particles on the cumulative distribution curve are smaller than the particle size; Dv90 means that 90% of the particles on the cumulative distribution curve are smaller than the particle size; S3) the recovered graphite screened out of the secondary screening is screened three times, and the indicators of the three screenings are: Dv10, Dv50, Dv90 graphitization degree and residual carbon content; The recycled graphite screened three times must meet the index requirements of Dv50 and at least two of the indicators of Dv10, Dv90, degree of graphitization and residual carbon content; S4) The recycled graphite screened out three times is used to make negative electrode sheets, and is matched with positive electrode sheets to make soft-pack batteries, and electrochemical tests are performed to determine whether to use it or not based on the electrochemical test results.

2. The method for screening recycled graphite according to claim 1, characterized in that: In step S2): D=1.4-1.8; The tap density is recorded as TD, TD ≥ 0.95 g / cm 3 ; The specific surface area is recorded as SSA, SSA ≤ 2.0m 2 / g; The gram capacity is recorded as C, C ≥ 340 mAh / g; The first effect was recorded as CE, and CE≥92.0%.

3. The method for screening recycled graphite according to claim 2, characterized in that: In step S3), Dv10≥5um, 11.5um≤Dv50≤15.5um, 24um≤Dv90≤35um, graphitization degree≥93.0%, 1.0%≤residual carbon content≤3.0%.

4. The method for screening recycled graphite according to claim 1, 2 or 3, characterized in that: In step S3), the three screening indicators also include key powder parameter A; Wherein, D represents particle size distribution, TD represents tap density, SSA represents specific surface area, C represents gram capacity, and CE represents first effect.

5. The method for screening recycled graphite according to claim 4, characterized in that: Key powder parameter A≥5.

27.

6. The method for screening recycled graphite according to claim 2, characterized in that: TD≥1.05g / cm 3 ,SSA≤1.8m 2 / g,C≥343mAh / g,CE≥93.0%。 7. The method for screening recycled graphite according to claim 3, characterized in that: Dv10≥6um, 12.5um≤Dv50≤14.5um, 26um≤Dv90≤30um, graphitization degree≥93.5%, 1.5≤residual carbon content≤2.5%.

8. A method for making a negative electrode sheet using the recycled graphite selected according to claim 3, characterized in that: The following steps are involved: J1) homogenizing the recovered graphite, dispersant, conductive agent, binder, and solvent according to processing requirements to obtain a negative electrode slurry; J2) coating the negative electrode slurry on the current collector, baking it in an oven, rolling it, and then slitting and die-cutting it according to specifications to obtain the required negative electrode sheet.

9. The method for manufacturing a negative electrode sheet according to claim 8, characterized in that: In step J1), the dispersant is CMC, the conductive agent is Super P, and the binder is SBR; By mass percentage: recycled graphite: SUPER P: CMC: SBR = 96.2%: 0.8%: 1.2%: 1.8%, and the solvent is deionized water.

10. The method for manufacturing a negative electrode sheet according to claim 8 or 9, characterized in that: In step J1), the negative electrode slurry has a delivery viscosity of 2000-8000 mPa*s, a solid content of 42-46%, and a delivery fluidity of 0.5-3 min / kg; In step J2), the compaction density of the negative electrode slurry after roller pressing is 1.5-1.6 g / cc.